The Pedicled Latissimus Dorsi Flap in Head and Neck Reconstruction: An Old Method Revisited - Wilkman, Tommy; Suominen, Sinikka; Back, Leif; Vuola, Jyrki; Lassus, Patrik (Journal of Reconstructive Microsurgery, 2014)
In head and neck cancer patients with significant comorbidities, the reconstructive options are limited, and there is a need for a safe alternative for microvascular flaps without compromising flap size. During the study period, 331 head and neck cancer patients were reconstructed with microvascular tissue flaps. Ten patients requiring large resections were considered to have high risks for long surgery and to be poor candidates for free tissue transfer and thus were reconstructed with a subpectorally tunneled pedicled latissimus dorsi (SP-LD) flap. The flap was raised simultaneously with the tumor resection and tunneled to the head and neck region. The flap was used for reconstruction of oral, mandibular, pharyngeal, or neck defects. Median follow-up was 3.6 years. Median duration of surgery was 7 hours and 17 minutes, and total hospital stay was 20 days. During the follow-up, four patients died of their disease and one from another cause (median of 329 days). We were able to perform large tumor resections with a curative intent and reconstruct major defects in high-risk head and neck cancer patients with a SP-LD flap. It possesses many of the characteristics of a free flap with the benefits of a shorter operation time and less perioperative risk.
Keywords: head and neck surgery; reconstruction; latissimus dorsi musculocutaneous flap